2011
DOI: 10.1155/2011/951043
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium Inhalation in a Mouse Model for the Understanding of Air‐Suspended Particle Systemic Repercussion

Abstract: There is an increased concern about the health effects that air-suspended particles have on human health which have been dissected in animal models. Using CD-1 mouse, we explore the effects that vanadium inhalation produce in different tissues and organs. Our findings support the systemic effects of air pollution. In this paper, we describe our findings in different organs in our conditions and contrast our results with the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 48 publications
(63 reference statements)
10
34
0
Order By: Relevance
“…We found that vanadium exposed mice presented a shift of the normal cortex-medulla relationship, showing a much thinner medulla and the presence of medulla-like areas within the cortex regions. These changes suggest an alteration of the immune response [69,89]. In addition to these findings we have reported a decrease in the presence of CD11c, a dendritic cell marker, and MHCII an antigen presenting cell marker, in the thymus of vanadium-exposed mice.…”
Section: Immunotoxicity Of Metalssupporting
confidence: 70%
See 2 more Smart Citations
“…We found that vanadium exposed mice presented a shift of the normal cortex-medulla relationship, showing a much thinner medulla and the presence of medulla-like areas within the cortex regions. These changes suggest an alteration of the immune response [69,89]. In addition to these findings we have reported a decrease in the presence of CD11c, a dendritic cell marker, and MHCII an antigen presenting cell marker, in the thymus of vanadium-exposed mice.…”
Section: Immunotoxicity Of Metalssupporting
confidence: 70%
“…Thus, genotoxic mutagenic events precede and therefore are the source of cellular malignancy [63]. Studies indicate that nickel induces chromosome aberrations in rats [64]; cadmium [65] and lead [66] causes single strand breaks and alkali-labile sites in mouse cells; in rats uranium causes double strand breaks [67]; iron induces in mice chromosome aberrations and micronuclei; in human beings vanadium produces bases oxidation and micronucleus [68], but in mice produces single strand breaks and micronucleus too [69,70]. Conversely to others metals, titanium showed no adverse effects on DNA in mice cells [71].…”
Section: Genotoxicity and Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vanadium (V) is adsorbed into PM and by inhalation reaches the systemic circulation exerting its toxic effect in other organs and tissues (Dockery & Pope 1994;Barceloux 1999). Adverse effects by V exposure in reproductive, nervous, urinary, respiratory and hematopoietic systems have been reported (Aragon et al 2005;Gonzalez-Villalva et al 2009;Fortoul et al 2011Fortoul et al , 2014aRodriguez-Lara et al 2013b;Walters et al 2014). Nevertheless, the effects of V on the immune system are not very well studied and many of the reported results have often been contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Inhalation exposure was performed as described in Fortoul et al (2011). In brief, the wholebody exposures were performed with V 2 O 5 (99.99%, Sigma, St. Louis, MO) as a 0.02-M suspension in saline.…”
Section: Vanadium Exposuresmentioning
confidence: 99%